The Relationship between Organizational Citizenship Behavior and Professional Behavior Mediated by Nurses\' Physical Health - B Zahedpasha (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Organizational citizenship behavior is a performance beyond job duties that can lead to professional behavior and improve the performance of the organization and the quality of services. Considering that the physical health of nurses is one of the requirements for the quality of their performance, this study was conducted to investigate the relationship between organizational citizenship behavior and professional behavior mediated by nurses' physical health. METHODS: This cross-sectional study was performed in 2019 among 350 nurses working in Amirkola Children's Hospital, and Yahyanejad, Shahid Beheshti and Ayatollah Rouhani Hospitals affiliated to Babol University of Medical Sciences. Using a four-section questionnaire, including Demographic Characteristics Questionnaire, Podsakoff Organizational Citizenship Behavior Scale (24 items with a score range of 24-120), Goz Nursing Professional Behavior Scale (27 items with a score range of 27-135) and Physical Health Questionnaire (14 items with a score range of 14-98), the required data were collected and evaluated. FINDINGS: There were 245 female nurses (70%) and 105 male nurses (30%). The age of 59.4% of subjects was in the rage of 30-39 years. The mean value of organizational citizenship behavior was 75.77±17.93 and the mean value of professional behavior was 102.30±18.27. The relationship between organizational citizenship behavior and professional behavior was direct and significant (path coefficient=0.481, p<0.001). The mean value of physical health was 47.17±10.80 and physical health played a mediating role in the relationship between organizational citizenship behavior and professional behavior (p<0.05). CONCLUSION: The results of the study showed that there was a direct relationship between organizational citizenship behavior and professional behavior and the mediating role of nurses' physical health in this regard was confirmed.